Undiagnosed prediabetes in Mexican adolescents under poverty in contexts affected by collective violence: A clinical comparison among health services users and hidden population - Hernández-Montoya, Dewi; Cedillo-Escobar, Elsie E.; Esparza-Aguilar, Marcelino; Muñoz-Torres, Abril Violeta (Frontiers in Nutrition, 2022)
Introduction. The epidemiological pattern of prediabetes on adolescents is understudied. In Mexico, adolescents are exposed to social adversity conditions, including poverty and violence. To understand their clinical profiles and the way in which the social determinants of health impose health services access barriers is important to address detection, in those that, by its vulnerability, remain as hidden population. Aim. To describe the undiagnosis of prediabetes of Mexican adolescents under poverty in violent contexts and to compare the clinical features among health services users and hidden population. Methods. This cross-sectional study included 371 adolescents from difficult access locations in violent contexts. Poverty and lack of health services access, and perceived vulnerability were determined in all sample. Endocrine markers (BMI, HOMA-IR, HbA1c, cortisol) were measured in those with high violence perception. Results. The 61.7% of the adolescents had a suburban grid and urban cluster residence. A 77.7-85.7% of them belonged to locations with 35 to 50% of their population living below poverty line. A 40-75% had lack of 10 to 20% access to health services. The 18.8% had a high perceived vulnerability due collective violence and were screened. The 61.9% of respondents were newly diagnosed with prediabetes and showed the worst HbA1c (p=0.001) compare to the health services subsample, which showed the highest BMI (p=0.031) and insulin resistance (p=0.025). Conclusion. There is a prediabetes hidden population living in violent contexts under poverty. These social determinants promote poor outcomes in perceived vulnerability and endocrine response and represent barriers to access to health services.